PENGARUH WAKTU SETELAH PENYEMBELIHAN ITIK TERHADAP KARAKTERISTIK SOSIS DENGAN BINDER TEPUNG KACANG TOLO (Vigna unguiculata L.Walp) - , REGINA RATIH RATRININGTYAS; , Ir. Sri Kanoni, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Duck is one protein sourced flow that the process is still limited because of its highly fat contained and its smell. One of alternatives of the duck meat process is sausage production with fresh meat as the main ingredient. The meats distributed at markets are commonly low in quality because they have encountered postmortem phase, for that the knowledge of the effect of postmortem period time on meat quality is needed. The other component in the sausage production is binder, cowpea flour is the ingredient that contains high protein, that makes it potential as skimmed milk binder substitute tp improve stability of sausage emulsion. This study was aimed to consider chemical, physics, characteristics, liking value, and descriptive substitution of cowpea flour (0%:100%)